THE PROBLEMS TO PROVIDE THE PRINCIPLE OF SAVING THE BEST INTEREST OF CHILD BY COURTS IN THE REPUBLIC OF ARMENIA - Zargaryan, Hayarpi (State and Law, 2022)
The main purpose of foreign courts is to ensure that the best interests of the child are exercised, interpreted, and investigated in the best interests of the child. The best interests of children are ignored by the courts, so the main purpose of the study is  to identify the reasons for it, to ensure the detection of such violations by the state, to give them a legal assessment.This article covers the case law of the European Court of Human Rights, which analyzes the concept of "best interests of the child" as a substantive law, a procedural law, a procedural principle, and a procedural rule.
Keywords: The best interests of the child; family life; the Supreme Judicial Council; the Ethics and Disciplinary Committee of the General Assembly of Judges of the Republic of Armenia; the place of residence of the child; the right of the child to move freely; the right to respect for family life